Decolonizing Development Studies: Pedagogic Reflections - Cornwall, Andrea (Radical Teacher, 2019)
Even more than the discipine that was so famously labelled the ’handmaiden of colonialism’ (Asad, 1973), Development Studies has been associated in critique with the perpetuation of colonial and neocolonial thinking and practice. What would it take to decolonise the teaching of Development Studies? Is it even possible? This article takes an experiential look at an experimental interactive workshop-style first year undergraduate introductory international development module. The module started off from the place I was at, as a professor who had newly come to higher education from a career on the margins of the development industry. I brought with me experience and knowledge, but also deep cyncism and negativity. I established the module as a mode of dialogue with my students, who wrote regular blogs instead of essays. Over the years, as I engaged with their work and worldview, my own shifted. I came to reframe development, and with this, to shift my own attempts to decolonise my teaching. I explore this journey, reflecting on where it took me and on some of the lessons I learnt from this experience.